Composite polyaluminum chloride water treatment agent and preparation method thereof
By combining polyaluminum chloride with modified sepiolite fibers and loading multi-order anions and auxiliary flocculants, the problems of unstable chemical properties and poor flocculation effects of polyaluminum chloride water treatment agents are solved, and higher structural stability and pollutant removal efficiency are achieved.
Patent Information
- Application Number
- CN202510132955.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-02-06
AI Technical Summary
Polyaluminum chloride water treatment agents have problems such as unstable chemical properties, unstable flocculation effect, and poor effect of removing metal impurities.
By combining polyaluminum chloride with modified sepiolite fibers and loading multi-order anions and auxiliary flocculants in the composite material, a water treatment agent with higher structural stability and adsorption capacity is formed.
It improves the structural stability and flocculation effect of polyaluminum chloride, enhances the adsorption and removal of pollutants, and improves the long-term stability and application range of water treatment agents.
Smart Images

Figure BDA0005262223260000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment agents, and in particular relates to a composite polyaluminium chloride water treatment agent and a preparation method thereof. Background Art
[0002] With the development of industry and the improvement of human living standards, water consumption is increasing and water pollution is becoming increasingly serious. Flocculation sedimentation is simple and easy to operate, with high separation efficiency. It is an important method for solid-liquid separation of particles that are difficult to settle in the water treatment industry. The properties of the flocculant also directly affect the final flocculation effect, which in turn affects the subsequent process and the quality of the effluent.
[0003] Among them, polyaluminum chloride is a new type of high-efficiency inorganic polymer flocculant. Compared with traditional inorganic flocculants, polyaluminum chloride has more superior performance, greatly reduced dosage, shorter sedimentation time, and a wider range of suitable water addition. It is now widely used in raw water treatment as a water treatment agent.
[0004] However, there are still some problems with using polyaluminium chloride as a water treatment agent. For example, its unstable chemical properties will affect its use effect; excessive addition of polyaluminium chloride will lead to an increase in the amount of sludge generated in the water treatment system, posing a challenge to the treatment capacity of the sludge dewatering system; the flocs formed are small and the turbidity removal effect is not ideal.
[0005] Therefore, some studies have been conducted to compound organic flocculants with polyaluminium chloride to enhance the flocculation effect of polyaluminium chloride and improve the problems of polyaluminium chloride. However, the water treatment agent obtained by compounding still has problems such as unstable flocculation effect, weak ability to remove metal impurity ions in sewage and unstable structure. Summary of the invention
[0006] The object of the present invention is to provide a composite polyaluminium chloride water treatment agent and a preparation method thereof, so as to solve the problems of unstable chemical properties, unstable flocculation effect and poor removal effect of metal impurity ions of the polyaluminium chloride water treatment agent.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] In a first aspect, the present invention provides a composite polyaluminium chloride water treatment agent, comprising the following raw materials in parts by weight:
[0009] 100 parts of polyaluminium chloride;
[0010] 30-50 parts of modified sepiolite fiber;
[0011] Auxiliary flocculant 10-20 parts;
[0012] 15-25 parts of polyvinyl alcohol;
[0013] The modified sepiolite fiber is loaded with multi-order anions; the multi-order anions include one or a combination of phosphate ions, silicate ions and carbonate ions.
[0014] By adopting the above technical scheme, modified sepiolite fiber is added in the composite polyaluminium chloride water treatment agent of the present invention, and sepiolite fiber is a kind of natural mineral fiber, has unique layered and chain-like transition structure, and compared with general sepiolite, the sepiolite of fiber structure has larger specific surface area, adsorption capacity and ion exchange capacity. When compounded with polyaluminium chloride, there are a large number of active sites in the modified sepiolite fiber layered structure unit, such as silanol, and more complicated pore structure is also possessed, polyaluminium chloride molecules can be physically adsorbed, and polyaluminium chloride is prevented from prematurely gathering or precipitation, and the linear structure of sepiolite fiber itself can help bridge polyaluminium chloride molecules, form a larger network structure, contribute to maintaining the morphological integrity of polyaluminium chloride, so as to improve the structural stability and chemical stability of polyaluminium chloride. And it can also be used as a heterogeneous nucleation center, promote aluminum hydroxide colloidal particles to form and deposit on its surface, improve the floc volume formed, accelerate sedimentation velocity, improve turbidity removal rate, and improve stability.
[0015] At the same time, the modified sepiolite fiber also has strong adsorption and ion exchange capacity. There are more acidic and alkaline centers on the surface, which can help adsorb pollutants in the water. It can also change its interlayer spacing and surface properties through ion exchange, enhance the adsorption capacity of pollutants, and improve the flocculation effect of the water treatment agent. In addition, the modified sepiolite fiber can make up for the performance defects of polyaluminum chloride, and use the exchange adsorption capacity to remove some impurity metal ions in sewage, while not affecting the properties of polyaluminum chloride itself, thereby enhancing the ability of the obtained water treatment agent to remove metal impurity ions.
[0016] The polyaluminium chloride compounded with modified sepiolite fiber can maintain a relatively stable crystal structure even under adverse conditions, which can broaden the application scope of the composite polyaluminium chloride water treatment agent and improve the chemical stability of polyaluminium chloride.
[0017] The modified sepiolite fiber is also loaded with multi-order anions, which can enhance the adsorption capacity of the sepiolite fiber, and the multi-order anions can enhance the structural stability by forming a more complex complex with the chloride ions in polyaluminium chloride. The addition of anions can also prevent the further hydrolysis of polyaluminium chloride, which is beneficial to maintaining the stability of polyaluminium chloride. Furthermore, the introduction of multi-order anions can reduce the positive charge density of the original polyaluminium chloride, thereby weakening the electrostatic repulsion between particles, playing a role in charge neutralization and adsorption bridging, making it easier for the particles formed by flocculation to aggregate together to obtain larger flocs, improving the stability of the flocculation effect, and facilitating the solid-liquid separation step in post-processing.
[0018] Preferably, the multi-stage anions are a combination of phosphate ions, silicate ions and carbonate ions in a molar ratio of (0.4-0.6):(0.3-0.5):(0-0.2).
[0019] More preferably, the multi-stage anions are a combination of phosphate ions, silicate ions and carbonate ions in a molar ratio of 0.5:0.4:0.1.
[0020] By adopting the above technical scheme, the multi-stage anions loaded in the modified sepiolite fiber of the present invention are a combination of phosphate ions, silicate ions and carbonate ions, and the phosphate ions combined with silicate ions can avoid the further hydrolysis of polyaluminium chloride, reduce the formation of high polymerisation or gelled aluminium hydroxide, thereby avoiding unnecessary precipitation formation, and improving the stability of the modified sepiolite fiber composite polyaluminium chloride structure. At the same time, the phosphate ions can adjust the pH value together with the carbonate ions, maintain a good flocculation environment, and can play a certain buffering role to avoid environmental impact. The silicate ions can help maintain a good deturbidity capability under the stable pH range maintained by the phosphate ions and carbonate ions, and improve the sewage treatment effect of the water treatment agent.
[0021] At the same time, the composite multi-stage anions can enhance the adsorption bridging effect by increasing the coordination and complexing ability. Among them, the phosphate ion has a strong coordination ability and can form a stable complex with the hydrolysis product of polyaluminum chloride. The silicate ion can establish a hydrogen bond with it, which can expand the spatial size of the flocs, thereby increasing the sedimentation rate and further improving the purification capacity of the composite polyaluminum chloride water treatment agent.
[0022] Preferably, the raw materials of the modified sepiolite fiber include sepiolite fiber, tannic acid and water-soluble salt in a mass ratio of 1:(3.5-4):(0.3-0.4).
[0023] Preferably, the water-soluble salt includes a combination of one or more of water-soluble phosphates, water-soluble silicates and water-soluble carbonates.
[0024] More preferably, the water-soluble phosphate includes a combination of one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium pyrophosphate and sodium hexametaphosphate.
[0025] More preferably, the water-soluble silicate includes a combination of one or more of sodium silicate, potassium silicate and lithium silicate.
[0026] More preferably, the water-soluble carbonate includes a combination of one or more of sodium carbonate, potassium carbonate, ammonium carbonate and ammonium bicarbonate.
[0027] Preferably, the modified sepiolite fiber is prepared according to the following method:
[0028] A water-soluble salt and tannic acid are prepared into a reaction aqueous solution, sepiolite fibers are added into the reaction aqueous solution, stirred and mixed for 10 to 30 minutes, the pH value of the solution is adjusted to 7.5 to 8.0, the temperature is increased to 60 to 65° C., stirred and reacted for 2 to 3 hours, and finally dried, roasted and ground to obtain modified sepiolite fibers.
[0029] By adopting the above technical scheme, a large number of silanol groups in the sepiolite fiber can form hydrogen bonds or covalent bonds with the phenolic hydroxyl groups or carboxyl groups in the tannic acid molecules, and the tannic acid is fixed on the surface of the sepiolite fiber, thereby modifying the surface of the sepiolite fiber. The additional functional groups provided by the tannic acid can increase the number of active sites on the surface of the sepiolite fiber, help load multi-stage anions, and react to obtain a more stable complex, maintain a high adsorption efficiency, and will not easily detach from the surface of the sepiolite fiber during the use of the water treatment agent. In addition, the sepiolite fiber modified with tannic acid has higher structural integrity and stability, so that the obtained composite polyaluminum chloride has better physical properties.
[0030] Tannic acid can also participate in the coagulation process of polyaluminium chloride, promote the formation of flocs through adsorption and bridging, and help form a more compact and stable floc structure. Moreover, since tannic acid is fixed on the modified sepiolite fiber, it can greatly reduce the interaction between tannic acid and polyaluminium chloride and colloidal particles, and reduce the adverse effect on coagulation efficiency. At the same time, tannic acid can also form a relatively stable complex with metal ions, improving the ability of the obtained water treatment agent to remove impurity metal ions.
[0031] Preferably, the sepiolite fiber is pretreated; the pretreatment process includes: adding the sepiolite fiber to a strong acid solution, stirring and shaking for 4 to 6 hours, then raising the temperature to 90 to 100° C. to activate for 2 to 3 hours, and finally calcining at 550 to 600° C. for 2 to 3 hours.
[0032] Preferably, the strong acid solution includes a hydrochloric acid aqueous solution and a sulfuric acid aqueous solution with a mass fraction of 15-25%.
[0033] Preferably, the solid-liquid ratio of sepiolite fiber to strong acid solution is 1:(8-10).
[0034] By adopting the above technical solution, the sepiolite fiber is also pretreated with a strong acid before modification. The pretreatment can effectively remove impurities on the surface and in the internal pores of the sepiolite fiber, improve the adsorption capacity of the sepiolite fiber, and expose more active sites, thereby enhancing the interaction between tannic acid and sepiolite fiber and enhancing the adsorption efficiency.
[0035] Preferably, the auxiliary flocculant includes any one of chitosan, sodium carboxymethyl starch and pectin.
[0036] More preferably, the auxiliary flocculant is pectin.
[0037] By adopting the above technical scheme, in order to stabilize the flocculation of polyaluminium chloride, the addition of auxiliary flocculants can strengthen the flocculation process, connect fine colloidal particles into larger flocs through bridging action, increase the floc volume, improve the solid-liquid separation efficiency, and also improve the ability of water treatment agents to remove chroma and turbidity.
[0038] Furthermore, the auxiliary flocculant of the present invention is pectin. Compared with other auxiliary flocculants, pectin has a longer molecular weight, and the active groups contained in the molecular chain can establish stronger bridge connections to form a more stable and solid floc structure. Moreover, because pectin has both hydrophilic groups and hydrophobic segments, it can promote the flocculation process while adsorbing organic pollutants, thereby achieving a better flocculation effect.
[0039] Preferably, the molecular weight of polyvinyl alcohol is 5.0×10 4 ~7.0×10 4 .
[0040] By adopting the above technical scheme, a good flocculation effect and water treatment effect can be achieved by loading a modified sepiolite fiber with multiple anions and compounding polyaluminium chloride under the action of an auxiliary flocculant. However, in the face of extreme water quality or long-term stirring, the stability will decrease, and the composite polyaluminium chloride and the auxiliary flocculant have a tendency to separate from the modified sepiolite fiber. Therefore, polyvinyl alcohol is also added in the process of compounding polyaluminium chloride. The polyvinyl alcohol itself has good film-forming property and adhesion, and can react with the multiple active groups on the modified sepiolite fiber to enhance the structural strength of the obtained composite material, play a certain protective role, avoid the separation of polyaluminium chloride, and also block the adverse effects of the outside world on the water treatment agent. And the large amount of polar groups and adhesion contained in polyvinyl alcohol also make it possible to fix organic pollutants by physical adsorption or chemical cross-linking in the water treatment process, improve the attraction of the water treatment agent to pollutants, thereby improving the flocculation efficiency and water treatment efficiency of the water treatment agent.
[0041] In a second aspect, the present invention provides a method for preparing a composite polyaluminium chloride water treatment agent, comprising the following process steps:
[0042] S1. The polyaluminium chloride and modified sepiolite fibers were mixed evenly, an auxiliary flocculant was added, stirring and mixing was continued, wet ball milling was performed, and the premix was obtained after drying;
[0043] S2. Add polyvinyl alcohol and water to the premix, raise the temperature to 35-45° C., stir and mix for 2-3 hours, and finally dry to obtain a composite polyaluminum chloride water treatment agent.
[0044] Preferably, the solid-liquid ratio of wet ball milling is 1:(5-6); and the wet ball milling time is 1-2 hours.
[0045] Preferably, the mass ratio of water to polyvinyl alcohol is (0.9-1.2):1.
[0046] Beneficial effects of the present invention:
[0047] 1. The composite polyaluminium chloride water treatment agent of the present invention is mainly to compound polyaluminium chloride with modified sepiolite fiber. The fiber structure of sepiolite fiber can provide sufficient adsorption sites and bridging structure for polyaluminium chloride, improve the structural stability of polyaluminium chloride, and enhance the adsorption capacity of pollutants. The modified sepiolite fiber of the present invention is also loaded with multi-order anions, which can enhance the structural stability by forming a more complex complex with the chloride ions in polyaluminium chloride. The combination of multiple anions can enhance the effect of charge neutralization and adsorption bridging, so that the particles formed by flocculation are more easily aggregated to obtain larger flocs, thereby improving the stability of the flocculation effect.
[0048] 2. Tannic acid is also fixed on the surface of the modified sepiolite fiber of the present invention, which can improve the adsorption rate of multi-order anions on the one hand, and on the other hand can cooperate with polyaluminum chloride to help form a more compact and stable floc structure, and can also complex metal ions to improve the ability of the composite water treatment agent to remove metal impurities.
[0049] 3. The composite polyaluminium chloride water treatment agent of the present invention is also added with an auxiliary flocculant, which can strengthen the flocculation process, improve the solid-liquid separation efficiency and the ability to remove turbidity; and polyvinyl alcohol is also added to protect the composite polyaluminium chloride water treatment agent from being easily decomposed and separated during the water treatment process, and can also enhance the attraction of the obtained water treatment agent to organic pollutants and improve the flocculation efficiency. DETAILED DESCRIPTION
[0050] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] Preparation Example
[0052] Preparation Example 1: A modified sepiolite fiber is prepared according to the following method:
[0053] 10 g of sepiolite fiber was passed through a 200 mesh sieve, added to 100 mL of a 20% hydrochloric acid aqueous solution, stirred and shaken for 5 h, then the temperature was raised to 95 ° C for activation for 2 h, and finally calcined at 600 ° C for 2 h to obtain the pretreated sepiolite fiber;
[0054] 3 g of water-soluble salt and 38 g of tannic acid were prepared into a reaction aqueous solution with a mass fraction of 50%. 10 g of the sepiolite fiber obtained above was added to the reaction aqueous solution. After stirring and mixing for 20 minutes, the pH value of the solution was adjusted to 7.5, the temperature was increased to 65°C, and the reaction was stirred for 2 hours. Finally, the modified sepiolite fiber was obtained by drying, calcining and grinding.
[0055] The water-soluble salt is a combination of sodium dihydrogen phosphate, sodium silicate and sodium carbonate in a molar ratio of 0.5:0.4:0.1.
[0056] Preparation Example 2, a modified sepiolite fiber, is different from Preparation Example 1 only in that the added amount of water-soluble salt is 3 g and the added amount of tannic acid is 35 g.
[0057] Preparation Example 3, a modified sepiolite fiber, is different from Preparation Example 1 only in that the amount of water-soluble salt added is 4 g, and the amount of tannic acid added is 45 g.
[0058] Preparation Example 4, a modified sepiolite fiber, is different from Preparation Example 1 only in that the water-soluble salt is a combination of sodium dihydrogen phosphate and sodium silicate in a molar ratio of 0.6:0.4.
[0059] Preparation Example 5, a modified sepiolite fiber, is different from Preparation Example 1 only in that the water-soluble salt is a combination of sodium dihydrogen phosphate, sodium silicate and sodium carbonate in a molar ratio of 0.4:0.4:0.2.
[0060] Preparation Example 6, a modified sepiolite fiber, is different from Preparation Example 1 only in that the water-soluble salt is a combination of sodium silicate and sodium carbonate in a molar ratio of 0.8:0.2.
[0061] Preparation Example 7, a modified sepiolite fiber, is different from Preparation Example 1 only in that the water-soluble salt is a combination of sodium dihydrogen phosphate and sodium carbonate in a molar ratio of 0.8:0.2.
[0062] Preparation Example 8, a modified sepiolite fiber, is different from Preparation Example 1 only in that the water-soluble salt is sodium dihydrogen phosphate.
[0063] Preparation Example 9, a modified sepiolite fiber, is different from Preparation Example 1 only in that the water-soluble salt is sodium silicate.
[0064] Preparation Example 10, a modified sepiolite fiber, is different from Preparation Example 1 only in that the water-soluble salt is sodium carbonate.
[0065] Preparation Example 11, a modified sepiolite fiber, is different from Preparation Example 1 only in that the amount of water-soluble salt added is 2 g.
[0066] Preparation Example 12, a modified sepiolite fiber, is different from Preparation Example 1 only in that the amount of water-soluble salt added is 5 g.
[0067] Preparation Example 13, a modified sepiolite fiber, is different from Preparation Example 1 only in that the amount of tannic acid added is 30 g.
[0068] Preparation Example 14, a modified sepiolite fiber, is different from Preparation Example 1 only in that the amount of tannic acid added is 50 g.
[0069] Preparation Example 15, a modified sepiolite fiber, is different from Preparation Example 1 only in that tannic acid is not added.
[0070] Preparation Example 16, a modified sepiolite fiber, prepared according to the following method:
[0071] 3 g of water-soluble salt and 38 g of tannic acid were prepared into a reaction aqueous solution with a mass fraction of 50%. 10 g of sepiolite fiber (passed through a 200-mesh sieve) was added to the reaction aqueous solution. After stirring and mixing for 20 minutes, the pH value of the solution was adjusted to 7.5, the temperature was increased to 65°C, and the reaction was stirred for 2 hours. Finally, the modified sepiolite fiber was obtained by drying, calcining and grinding.
[0072] Preparation Example 17, a modified sepiolite fiber, is different from Preparation Example 1 only in that no water-soluble salt is added.
[0073] Preparation Example 18, a modified sepiolite fiber, is different from Preparation Example 1 only in that the sepiolite fiber is replaced by an equal amount of sepiolite powder.
[0074] Example
[0075] Example 1, a composite polyaluminium chloride water treatment agent, is prepared according to the following process steps:
[0076] S1. 100 g of polyaluminium chloride (Al2O3 ≥ 30%) and 40 g of the modified sepiolite fiber prepared in Preparation Example 1 were mixed uniformly, 15 g of pectin was added, and the mixture was stirred and wet-milled, wherein the solid-liquid ratio of the wet-milling was 1:5; the wet-milling time was 1.5 h, and the premix was obtained after drying;
[0077] S2. Add 20 g of polyvinyl alcohol (average molecular weight 6.0×10 4 ) and 20g of water, raise the temperature to 40°C, stir and mix for 2h, and finally dry to obtain a composite polyaluminum chloride water treatment agent.
[0078] Example 2, a composite polyaluminium chloride water treatment agent, is different from Example 1 only in that the amount of modified sepiolite fiber prepared in Preparation Example 1 added is 30 g; the amount of pectin added is 20 g; and the amount of polyvinyl alcohol added is 15 g.
[0079] Example 3, a composite polyaluminium chloride water treatment agent, is different from Example 1 only in that the amount of modified sepiolite fiber prepared in Preparation Example 1 added is 50 g; the amount of pectin added is 10 g; and the amount of polyvinyl alcohol added is 25 g.
[0080] Example 4, a composite polyaluminum chloride water treatment agent, is different from Example 1 only in that the modified sepiolite fiber prepared in Preparation Example 1 is replaced by an equal amount of modified sepiolite fiber prepared in Preparation Example 2.
[0081] Example 5, a composite polyaluminum chloride water treatment agent, is different from Example 1 only in that the modified sepiolite fiber prepared in Preparation Example 1 is replaced by an equal amount of the modified sepiolite fiber prepared in Preparation Example 3.
[0082] Example 6, a composite polyaluminum chloride water treatment agent, is different from Example 1 only in that an equal amount of modified sepiolite fibers prepared in Preparation Example 4 are used to replace the modified sepiolite fibers prepared in Preparation Example 1.
[0083] Example 7, a composite polyaluminum chloride water treatment agent, is different from Example 1 only in that an equal amount of modified sepiolite fibers prepared in Preparation Example 5 are used to replace the modified sepiolite fibers prepared in Preparation Example 1.
[0084] Example 8, a composite polyaluminum chloride water treatment agent, is different from Example 1 only in that the modified sepiolite fiber prepared in Preparation Example 1 is replaced by an equal amount of modified sepiolite fiber prepared in Preparation Example 6.
[0085] Example 9, a composite polyaluminum chloride water treatment agent, is different from Example 1 only in that an equal amount of modified sepiolite fibers prepared in Preparation Example 7 are used to replace the modified sepiolite fibers prepared in Preparation Example 1.
[0086] Example 10, a composite polyaluminum chloride water treatment agent, is different from Example 1 only in that the modified sepiolite fiber prepared in Preparation Example 1 is replaced by an equal amount of modified sepiolite fiber prepared in Preparation Example 8.
[0087] Example 11, a composite polyaluminum chloride water treatment agent, is different from Example 1 only in that the modified sepiolite fiber prepared in Preparation Example 1 is replaced by an equal amount of modified sepiolite fiber prepared in Preparation Example 9.
[0088] Example 12, a composite polyaluminum chloride water treatment agent, is different from Example 1 only in that the modified sepiolite fiber prepared in Preparation Example 1 is replaced by an equal amount of modified sepiolite fiber prepared in Preparation Example 10.
[0089] Example 13, a composite polyaluminum chloride water treatment agent, is different from Example 1 only in that the modified sepiolite fiber prepared in Preparation Example 1 is replaced by an equal amount of modified sepiolite fiber prepared in Preparation Example 11.
[0090] Example 14, a composite polyaluminum chloride water treatment agent, is different from Example 1 only in that the modified sepiolite fiber prepared in Preparation Example 1 is replaced by an equal amount of modified sepiolite fiber prepared in Preparation Example 12.
[0091] Example 15, a composite polyaluminum chloride water treatment agent, differs from Example 1 only in that an equal amount of modified sepiolite fibers prepared in Preparation Example 13 are used to replace the modified sepiolite fibers prepared in Preparation Example 1.
[0092] Example 16, a composite polyaluminum chloride water treatment agent, differs from Example 1 only in that an equal amount of modified sepiolite fibers prepared in Preparation Example 14 are used to replace the modified sepiolite fibers prepared in Preparation Example 1.
[0093] Example 17, a composite polyaluminum chloride water treatment agent, differs from Example 1 only in that an equal amount of modified sepiolite fibers prepared in Preparation Example 16 are used to replace the modified sepiolite fibers prepared in Preparation Example 1.
[0094] Example 18, a composite polyaluminium chloride water treatment agent, differs from Example 1 only in that an equal amount of chitosan is used to replace pectin.
[0095] Comparative Example
[0096] Comparative Example 1, a composite polyaluminium chloride water treatment agent, is different from Example 1 only in that the added amount of the modified sepiolite fiber prepared in Preparation Example 1 is 20 g.
[0097] Comparative Example 2, a composite polyaluminium chloride water treatment agent, is different from Example 1 only in that the added amount of the modified sepiolite fiber prepared in Preparation Example 1 is 60 g.
[0098] Comparative Example 3, a composite polyaluminum chloride water treatment agent, differs from Example 1 only in that an equal amount of modified sepiolite fibers prepared in Preparation Example 15 are used to replace the modified sepiolite fibers prepared in Preparation Example 1.
[0099] Comparative Example 4, a composite polyaluminum chloride water treatment agent, differs from Example 1 only in that an equal amount of modified sepiolite fibers prepared in Preparation Example 17 are used to replace the modified sepiolite fibers prepared in Preparation Example 1.
[0100] Comparative Example 5, a composite polyaluminum chloride water treatment agent, differs from Example 1 only in that an equal amount of modified sepiolite fibers prepared in Preparation Example 18 are used to replace the modified sepiolite fibers prepared in Preparation Example 1.
[0101] Comparative Example 6, a composite polyaluminum chloride water treatment agent, is different from Example 1 only in that an equal amount of sepiolite fibers is used to replace the modified sepiolite fibers prepared in Preparation Example 1.
[0102] Comparative Example 7, a composite polyaluminium chloride water treatment agent, differs from Example 1 only in that pectin is not added.
[0103] Comparative Example 8, a composite polyaluminium chloride water treatment agent, was prepared according to the following process steps:
[0104] 100g of polyaluminium chloride (Al2O3≥30%) and 40g of the modified sepiolite fiber prepared in Preparation Example 1 were mixed evenly, 15g of pectin was added, stirring and mixing were continued, and wet ball milling was performed, wherein the solid-liquid ratio of the wet ball milling was 1:5; the wet ball milling time was 1.5h, and a composite polyaluminium chloride water treatment agent was obtained after drying.
[0105] Performance testing
[0106] Sample preparation: Organic sewage from urban rivers was collected, with an influent COD content of 330 mg / L and Cu 2+ 43.2 mg / L, take 500 mL of the above sewage, add the composite polyaluminum chloride water treatment agent obtained in the embodiment and the comparative example, the dosage is 25 mg / L, stir for 15 minutes and then let it stand for 15 minutes, take the supernatant as a sample for testing:
[0107] 1. COD test: According to the relevant records in HJ 828-2017 "Determination of Chemical Oxygen Demand of Water Quality - Dichromate Method", the COD of the sample is tested and the CDO removal rate is calculated;
[0108] 2. Turbidity test: According to the relevant records in GB / T 13200-1991 "Determination of turbidity of water quality", the turbidity of the sample is tested;
[0109] 3. Cu 2+ Test: Determination of Cu in samples 2+ Content, calculate Cu 2+ Removal rate.
[0110] The above test results are shown in Table 1:
[0111] Table 1 Performance test results
[0112]
[0113] According to Table 1, in combination with Example 1, Example 13, Example 14 and Comparative Example 4, it can be seen that the COD removal rate and Cu 2+The removal rate is lower than that of Example 1, and the turbidity is increased. The performance of Comparative Example 4 is significantly reduced. The reason is that in Example 13, the content of multi-stage anions carried by the modified sepiolite fiber is reduced, the structural stability of polyaluminium chloride is reduced, and the charge neutralization and adsorption bridging effects of the water treatment agent are reduced, the removal efficiency is reduced, and the flocculation effect is poor, resulting in a decrease in the removal rate of the final composite polyaluminium chloride water treatment agent. In Comparative Example 4, the sepiolite fiber does not carry multi-stage anions, and the performance is more significantly reduced. In Example 14, the content of multi-stage anions carried is increased, which will lead to charge imbalance and is not conducive to flocculation.
[0114] Combining Example 1, Example 15, Example 16 and Comparative Example 3, it can be seen that the COD removal rate and Cu 2+ The removal rate was lower than that in Example 1, and the turbidity was increased, especially Cu 2+ The removal rate and turbidity change are more obvious. The reason is that in Example 15, the amount of tannic acid added to the modified sepiolite fiber during the preparation process is reduced, which will affect the stability of the multi-order anions of the load on the one hand, and on the other hand, the lack of tannic acid complexation and interaction, the flocculation effect and the removal rate of impurity metal ions are also reduced. In Comparative Example 3, tannic acid is not added, and the multi-order anions are easily separated from the surface of the modified sepiolite fiber during the water treatment process, reducing the synergistic enhancement effect of the composite polyaluminum chloride water treatment agent, and also greatly reducing the attraction and complexation between metal ions, and the water treatment capacity decreases more significantly. In Example 16, the amount of tannic acid added is increased, and the active sites on the modified sepiolite fiber are occupied in large quantities, which is not conducive to the composite between polyaluminum chloride and the auxiliary flocculant.
[0115] Combining Example 1 and Comparative Example 6, it can be seen that the COD removal rate and Cu 2+ The removal rate is significantly lower than that of Example 1, and the turbidity is significantly increased. The reason is that the sepiolite fiber in Example 6 has not undergone any modification treatment. Combined with the test results of Comparative Examples 3 and 4, it can be seen that the enhancement effects of tannic acid and multi-order anions synergize with each other, which can greatly improve the removal ability of the water treatment agent.
[0116] Combining Example 1 and Comparative Example 5, it can be seen that the COD removal rate and Cu 2+ The removal rate is lower than that of Example 1 and the turbidity is increased. The reason is that in Example 5, sepiolite fiber is replaced by sepiolite powder, and sepiolite powder does not have the unique fiber structure of the original sepiolite fiber, resulting in a decrease in the binding force with polyaluminum chloride, making it difficult to form a larger floc volume during the water treatment process, and the removal ability of the obtained water treatment agent is reduced.
[0117] Combining Example 1, Comparative Example 7 and Comparative Example 8, it can be seen that the COD removal rate and Cu 2+ The removal rate is lower than that of Example 1, and the turbidity is significantly increased. The reason is that no auxiliary flocculant is added in Example 7, the flocculation effect is reduced, and the treatment capacity of turbidity in sewage is also reduced; no polyvinyl alcohol is added in Example 8, which lacks the protective effect on the modified sepiolite fiber composite polyaluminum chloride structure, and reduces the attraction of the composite polyaluminum chloride water treatment agent to organic pollutants and metal ions in sewage, resulting in a decrease in the flocculation effect.
[0118] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0119] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A composite polyaluminium chloride water treatment agent, characterized in that: Including the following raw materials by mass: 100 parts of polyaluminium chloride; 30-50 parts of modified sepiolite fiber; Auxiliary flocculant 10-20 parts; 15-25 parts of polyvinyl alcohol; The modified sepiolite fiber is loaded with multi-stage anions; the multi-stage anions include one or a combination of phosphate ions, silicate ions and carbonate ions.
2. The composite polyaluminium chloride water treatment agent according to claim 1, characterized in that: The multi-stage anions are a combination of phosphate ions, silicate ions and carbonate ions in a molar ratio of (0.4-0.6): (0.3-0.5): (0-0.2).
3. The composite polyaluminium chloride water treatment agent according to claim 1, characterized in that: The raw materials of the modified sepiolite fiber include sepiolite fiber, tannic acid and water-soluble salt in a mass ratio of 1:(3.5-4):(0.3-0.4).
4. The composite polyaluminium chloride water treatment agent according to claim 3, characterized in that: The water-soluble salt includes a combination of one or more of water-soluble phosphates, water-soluble silicates and water-soluble carbonates.
5. The composite polyaluminium chloride water treatment agent according to claim 3, characterized in that: The sepiolite fiber is pretreated; The pretreatment process comprises: adding sepiolite fiber into a strong acid solution, stirring and shaking for 4 to 6 hours, then raising the temperature to 90 to 100° C. to activate for 2 to 3 hours, and finally calcining at 550 to 600° C. for 2 to 3 hours.
6. The composite polyaluminium chloride water treatment agent according to claim 3, characterized in that: The modified sepiolite fiber is prepared according to the following method: A water-soluble salt and tannic acid are prepared into a reaction aqueous solution, sepiolite fibers are added into the reaction aqueous solution, stirred and mixed for 10 to 30 minutes, the pH value of the solution is adjusted to 7.5 to 8.0, the temperature is increased to 60 to 65° C., stirred and reacted for 2 to 3 hours, and finally dried, roasted and ground to obtain modified sepiolite fibers.
7. The composite polyaluminium chloride water treatment agent according to claim 1, characterized in that: The auxiliary flocculant includes any one of chitosan, sodium carboxymethyl starch and pectin.
8. The composite polyaluminium chloride water treatment agent according to claim 1, characterized in that: The molecular weight of the polyvinyl alcohol is 5.0×10 4 ~7.0×10 4 .
9. A method for preparing a composite polyaluminium chloride water treatment agent according to any one of claims 1 to 8, characterized in that: The process steps include: S1. The polyaluminium chloride and modified sepiolite fibers were mixed evenly, an auxiliary flocculant was added, stirring and mixing was continued, wet ball milling was performed, and the premix was obtained after drying; S2. Add polyvinyl alcohol and water to the premix, raise the temperature to 35-45° C., stir and mix for 2-3 hours, and finally dry to obtain a composite polyaluminum chloride water treatment agent.
10. A method for preparing the composite polyaluminium chloride water treatment agent according to claim 9, characterized in that: The solid-liquid ratio of the wet ball milling is 1:(5-6); the wet ball milling time is 1-2h.
Citation Information
Patent Citations
High-efficiency decolorizing treatment agent for industrial waste water and preparation method thereof
CN101596444A
Modified sepiolite as well as preparation method and application thereof
CN113083218A
Treatment method of high-salt high-fluorine sulfur-containing wastewater
CN117735773A